Structural failure analysis of a river-crossing transmission line impacted by the super typhoon Rammasun. (October 2019) - An, Liqiang; Guan, Yongyu; Zhu, Zhijian; Wu, Jiong; Zhang, Ronglun
Abstract: Steel lattice towers are commonly used as supporting structures for overhead transmission lines. Extreme wind conditions like typhoons can cause significant damage on those steel towers and consequently jeopardize the safe operation of transmission lines. In the line sections where a river crossing is unavoidable, the steel lattice towers are designed to be much taller and stronger than regular towers owing to safety and operation considerations. In previous typhoon events in Hainan Province of China, none of the installed river-crossing towers have collapsed or experienced significant damages, except in the aftermath of super typhoon Rammasun in 2014, when two 95-m tall river-crossing suspension towers collapsed. This paper presents the structural failure analysis of these two collapsed lattice steel transmission towers: The improved genetic algorithm (IGA) was applied to solve the typhoon wind field model for improved resolution of wind records measured during the Rammasun event and based on of 10-min average wind speeds. The IGA used the field measurement data to generate time-varying typhoon key parameters that lead to a more accurate prediction of the wind field than the conventional method. Then a systematic procedure was developed to investigate the failure mechanism of steel lattice towers under fluctuating wind loads combined with rain loads with consideration of the aerodynamic characteristics of the transmission tower-line system. The results show that the root-cause of the structural failure of the two transmission towers was overstressing of the tower main leg members in the second panel above the ground. Based on the numerical simulation of typhoon wind loads and the structural failure analysis procedure applied in this study, a general reinforcement method of river-crossing towers is proposed and the implementation of a typhoon warning method is recommended to identify the potential risks in transmission lines and formulate corresponding typhoon emergency plans to reduce the losses caused by typhoons. Highlights: The failure of a river-crossing transmission line damaged by typhoon is analyzed. Improved genetic algorithm (IGA) method was innovatively introduced to solve the typhoon wind filed. Fluctuating characteristic and strong rainfall led to the tower collapse. A new transmission line typhoon warning method is proposed.